2018
DOI: 10.5782/2223-2621.2018.21.3.5
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationships among EFL Learners Willingness to Communicate, Communication Apprehension, Self-Perceived Competence and Emotional Intelligence

Abstract: This study focused on the relationships among language learners' communication-related variables including willingness to start a communication (WTC), self-perceived communication competence (SPCC), communication apprehension (CA) and different subcomponents of emotional intelligence (EI). To this end a battery of questionnaires (WTC=20 items, Personal Report of Communication Apprehension (PRCA=24), Self-Perceived Communication Competence (SPCC =12), Emotional quotient inventory (EQ-I=133)) were distributed am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In light of this circumstance, certain individuals who perceive anxiety may be hesitant, reticent and uneasy to express themselves in public scenarios. As per Güvendir et al (2020), Mehrpoor andSoeimani (2018), andGenc et al (2016), incapable individuals are duplicitous, unmotivated, and uncommunicative. Social, economic, political, and intellectual dimensions of a human being's life are influenced by public speaking anxiety (Güvendir et al, 2020;Elani-Shirvan & Talebzadeh, 2020).…”
Section: Background and Problem Statementmentioning
confidence: 97%
“…In light of this circumstance, certain individuals who perceive anxiety may be hesitant, reticent and uneasy to express themselves in public scenarios. As per Güvendir et al (2020), Mehrpoor andSoeimani (2018), andGenc et al (2016), incapable individuals are duplicitous, unmotivated, and uncommunicative. Social, economic, political, and intellectual dimensions of a human being's life are influenced by public speaking anxiety (Güvendir et al, 2020;Elani-Shirvan & Talebzadeh, 2020).…”
Section: Background and Problem Statementmentioning
confidence: 97%
“…It is reasonable to presume that learners with higher levels of emotional intelligence have low-level apprehension in foreign language communication. Mehrpoor and Soleimani ( 2018 ) examined the correlation between EFL learners' communication apprehension, emotional intelligence, and willingness to communicate. Their study revealed that emotional intelligence is regarded as an external stimulus for interpersonal communication.…”
Section: Literature Reviewmentioning
confidence: 99%